Data-driven process discovery and analysis : third IFIP WG 2.6, 2.12 International Symposium, SIMPDA 2013, Riva del Garda, Italy, August 30, 2013, Revised selected papers /: third IFIP WG 2.6, 2.12 International Symposium, SIMPDA 2013, Riva del Garda, Italy, August 30, 2013, Revised selected papers. (2015) - Unknown
No abstract available